Das Arzneimittelmarktneuordnungsgesetz aus kinder- und jugendpsychiatrischer Perspektive = The new German drug market law AMNOG from a child andadolescent psychiatry perspective - Dittmann, Ralf (Der Nervenarzt, 2016)
Background: The European Union (EU) regulation 1901/2006 plus the implementation of pediatric investigational plans by the European Medicines Agency (EMA) have contributed to more clinical studies in pediatric psychopharmacology. A new drug market law (AMNOG) has been in force in Germany since 2011 that requires an additional process of assessment of benefits of newly authorized medications by the Federal Joint Committee (Gemeinsamer Bundesausschuss, G‑BA), which also holds for medications licensed for pediatric populations. Objectives: Summary of early assessments of benefits for newly registered compounds in the treatment of psychiatric disorders and critical discussion from the perspective of child and adolescent psychiatry. Material and methods: Application and critical review of documents and written statements by various institutions and stakeholders related to assessment procedures and respective decisions by the G‑BA for these medications. Results and conclusion: Clearly differing requirements for study designs and outcome parameters characterize the conditions for market authorization and for the assessment of benefits. Further adjustments to the regulations in implementing the AMNOG appear to be essential, integrating agencies involved so far, complimented by expertise from regulatory agencies and medical scientific societies.
Gesehen am 02.04.2019